The Role of Image Schemas in Interpreting English Phrasal Verbs - Febriansyah, Gema; Zaim, Muhammad; Thahar, Harris Effendi (Pioneer: Journal of Language and Literature, 2024)
Phrasal verbs pose challenges for interpretation due to unpredictable meanings. This study examined how image schemas aid comprehension from linguistic and philosophical viewpoints. A literature review methodology integrated insights from cognitive linguistics, philosophy of language, and related fields to provide a comprehensive understanding. Linguistically, image schemas offer a cognitive framework for processing phrasal verbs by mapping meanings to embodied experiences. Philosophically, schemas reflect how language emerges from and shapes conceptualization. Comparative analysis showed linguistics emphasizes schemas' mental role in comprehension, while philosophy explores their existential significance. Results identified schemas like CONTAINER and PATH that extend metaphorically from physical interactions to abstract phrasal verb meanings. Linguistically, schemas provide a framework for analyzing structures and meanings. Philosophically, schemas reflect language's emergence from embodiment and influence on thought. Teaching implications were to connect phrasal verbs to familiar embodied experiences through schemas. Theoretical implications were that schemas are fundamental to thought and linguistic expressions. By synthesizing perspectives, this study enhanced understanding of the intricate cognitive mechanisms linking schemas to phrasal verbs. It highlighted implications for language education and advances in interdisciplinary inquiry into embodied cognition and communication.